Development and Validation of Deflazacort Tablets Using Uv Spectroscopic Method - Aashiyana Rai, D Vidya; Saini, Rita; Patil, Shivanand (Journal of Neonatal Surgery, 2025)
Deflazacort is used to treat inflammatory diseases and autoimmune diseases as it possesses anti-inflammatory and immunosuppressive properties. The synthetic corticosteroid treats some forms of cancer too. The aim of this study was to establish a simple, precise, and inexpensive procedure for deflazacort determination in tablet dosage forms by these tablets using UV spectroscopy. A rigorous spectrophotometric method was developed and optimised to maintain dependability in linearity, precision, and accuracy along with appropriate analytical range for pharmaceutical analysis. Major validation steps such as specificity, accuracy, precision, linearity, limit of detection (LOD), and lower limit of quantification (LOQ) in relation to the International Council for Harmonisation (ICH) guidelines was done.Absence of considerable interference with excipients cut s the strong specificity of excipient tablet formulation made it posses a high degree of specificity. Other accuracy and precision studies showed behaviours that were acceptable for intraday and interday variability. Validation for robustness was done which showed the method reliable under a varying number of experimental conditions. The developed UV spectrophotometric method for the determination of deflazacort tablets is accurate, precise, and appropriate for regular quality control exercises in the pharmaceutical industry. This method can be effectively employed to ensure the quality and consistency of the deflazacort tablet formulations